PENGARUH SWITCHING COSTS TERHADAP INERTIA DAN CALCULATIVE COMMITMENT STUDI PADA NASABAH CIMB NIAGA CABANG ITC FATMAWATI - Shadiq, Teuku Fajar (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2019)
The purpose of this study is to examine how the mutual influence between Switching Costs is represented by five variables (benefit lost costs, uncertainty costs, evaluation costs, learning costs and Sunk costs) with Inertia and Calculative Commitment. The objective of this research was to analyze whether there is an impact between the Switching Cost on Inertia and Calculative Commitment which were significantly. This paper presents and develops a model that will articulate and classify the behavior of consumers in the purchase of financial products and services. The theoretical insights generated by this model are then used to examine research data obtained from questionnaires with centralized variables and focus on consumer attitudes towards financial service providers and their financial products. The importance of trust is not explicitly recognized but the relationship between trust and risk largely determines the behavior of a customer Aldas-Manzano et al. (2009). The design of this research applied multiple regression, hypothesis testing of validity (T-test and correlation) and hypothesis testing of reliability (Cronbach’s Alpha). Data analysis used in this research was primary data in which the population of this study is CIMB Niaga ITC Fatmawati branch office in South Jakarta. This research was carried out by distributing 200 questionnaires with samples customers who are over three years as a customer and maintain balance actively. The result of this research concluded that there are variables of switching cost that affect are inertia and calculative commitment that is an important driver of behavioral customer. Product innovation competition among actors of financial services to attract new customers must calculate the commitment and customer resistance in the costs and risks that will be generated